Accelerazione. Riflessioni sulle temporalità della pandemia - Silvia Caianiello (Laboratorio dell'ISPF, 2020)
The speed of the Covid-19 pandemic has imparted an acceleration – a "variation of velocity in the time unity" – to multiple social processes: that of political decision making, that of science in search of medical protocols and treatments, that of the use of new technologies, that of political and biopolitical control techniques. But each of the different functional systems tackling the challenge of this global threat has its own rhythm and tempo, constrained by the nature of its own constitutive processes. How is this acceleration putting to test the extant social "time structures", and how is it altering the dynamics of their interactions? The conceptual tools developed by the critical theory of acceleration for interpreting the temporal paradoxes of late modernity may provide a key for reading the ongoing transformations, and help reasoning on the possible directions of this acceleration – in fact, as it is the case in physics, the direction of acceleration is not pregiven, it is rather the resultant of the directions and intensities of the forces which act upon a body.